2015
DOI: 10.1111/jgs.13672
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Management of Hypertension in Older Persons: Focus on African Americans

Abstract: Multiple clinical trials have demonstrated the beneficial effects of blood pressure (BP) reduction on cardiovascular morbidity and mortality, with most of the evidence in individuals aged 60 and older. Several guidelines have recently been published on the specific management of hypertension in individuals aged 60 and older, including in high-risk groups such as African Americans. Most recommend careful evaluation, thiazide diuretics and calcium-channel blockers for initial drug therapy in most African America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…We recognize that participation in such a healthcare system does not guarantee equal treatment; however, it can minimize disparate racial access. Another strength is that our data displays the added advantage of having cancer-specific outcomes especially since other common causes of mortality, including cardiovascular disease, also have racial disparities [27,28]. Unlike studies based only on cancer registry data, we included comorbidity data such as CKD.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that participation in such a healthcare system does not guarantee equal treatment; however, it can minimize disparate racial access. Another strength is that our data displays the added advantage of having cancer-specific outcomes especially since other common causes of mortality, including cardiovascular disease, also have racial disparities [27,28]. Unlike studies based only on cancer registry data, we included comorbidity data such as CKD.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Moreover, hypertension in African Americans begins earlier, is more severe, and more frequently associated with premature morbidity and mortality from its complications including coronary heart disease, heart failure, stroke, and end-stage renal disease (ESRD). [2-6] Racial/ethnic disparities in hypertension and related outcomes continue to pose immense challenges for affected individuals and the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…[3, 5, 7-14] Despite recommendations on prescription of antihypertensive therapies, achieving BP control remains problematic and data on optimal BP targets remain controversial. [1, 2, 6] The 2011-2012 National Health and Examination Survey (NHANES III) data suggested that 76% of US adults with hypertension were taking antihypertensives, with a higher percentage of African Americans (79.7%) than European Americans (76.6%). [1] Despite antihypertensive treatment, nearly 50% of U.S. adults with hypertension were not controlled to the currently recommended target of <140/90 mmHg.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations